2000
DOI: 10.1096/fj.00-0029com
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchanger‐dependent intracellular alkalinization is an early event in malignant transformation and plays an essential role in the development of subsequent transformation‐associated phenotypes

Abstract: In this study we investigate the mechanism of intracellular pH change and its role in malignant transformation using the E7 oncogene of human papillomavirus type 16 (HPV16). Infecting NIH3T3 cells with recombinant retroviruses expressing the HPV16 E7 or a transformation deficient mutant we show that alkalinization is transformation specific. In NIH3T3 cells in which transformation can be turned on and followed by induction of the HPV16 E7 oncogene expression, we demonstrate that cytoplasmic alkalinization is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
325
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(342 citation statements)
references
References 39 publications
10
325
0
7
Order By: Relevance
“…22 Along similar lines, Reshkin et al 31 have recently demonstrated that just as efficient Ras-mediated transformation requires activation of Rac, NHE-1 protein expression was equally implicated in malignant transformation and the development of the transformed phenotype. 32 Taken together, these findings suggest that, in addition to activation of the exchanger leading to alkaline pHi, redox regulation of NHE-1 gene expression could be critical in tumor cell formation. In particular, resistance of tumor cells to death triggers due to a slight increase in intracellular O 2 KÀ could be linked to the regulation of NHE-1 protein expression.…”
Section: Discussionmentioning
confidence: 83%
“…22 Along similar lines, Reshkin et al 31 have recently demonstrated that just as efficient Ras-mediated transformation requires activation of Rac, NHE-1 protein expression was equally implicated in malignant transformation and the development of the transformed phenotype. 32 Taken together, these findings suggest that, in addition to activation of the exchanger leading to alkaline pHi, redox regulation of NHE-1 gene expression could be critical in tumor cell formation. In particular, resistance of tumor cells to death triggers due to a slight increase in intracellular O 2 KÀ could be linked to the regulation of NHE-1 protein expression.…”
Section: Discussionmentioning
confidence: 83%
“…Since these initial observations, numerous studies have examined the role of NHE1 in cancer. NHE1-dependent intracellular alkalinization plays an important role in the development of a transformed phenotype, as inhibition of NHE1 activity prevents this [141]. In breast cancer and leukemic cells, inhibition of NHE1 exerts a protective effect against cancer, inducing apoptosis [142,143].…”
Section: Slc9a1-nhe1mentioning
confidence: 99%
“…At this level, lactate has a central role in promoting disordered growth by stimulating the production of hyaluronan and the expression of its membrane receptor, CD44, enhancing cell motility and extracellular matrix looseness (Stern et al, 2002). Equally important is the H þ extrusion and the extracellular acidification brought not only by MCT4 (Gallagher et al, 2007) but also by Na þ /H þ exchangers (Reshkin et al, 2000) and other transmembrane channels whose levels are orchestrated in cancer cells (Pouyssegur et al, 2006). This strategy maintains intracellular alkalinization, exerting a positive feedback loop on glycolysis, through activation of 6-phosphofructo-1-kinase (Erecinska et al, 1995), whereas extracellular acidification triggers apoptosis in neighboring cells with normal p53 levels (Williams et al, 1999).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%